Un Pygmalion des Lumières ? - Chiara Gambacorti (Itinéraires, 2013)
“Eugénie de Franval” is generally seen as a celebration of incest; its tragic ending, as a simple concession to the rules of genre. If one reads this novella in conjunction with the rewritings of the myth of Pygmalion which were frequent during the 18th century, however, it is possible to illustrate how Franval’s “pygmalionesque” dream is coupled with a fantasy about exerting absolute power over the female beloved; a fantasy which the novella actually condemns, as confirmed if considered in parallel with La Philosophie dans le boudoir.